Pathophysiology of Cognitive Dysfunction Due to Decompression Sickness in Diver - Pratiwi, Baiq Bunga Citra; Suryantarini, Ni Wayan Puspa Wijaya; Satriawan, Wira; Jacob, Lusye Diana; Harahap, Herpan Syafii (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Cognitive impairment can occur due to factors that affect the structural and functional integrity of brain areas that specifically play a role in each cognitive domain. Severe cognitive impairment causes morbidity and mortality. One condition that can lead to complications such as a cognitive impairment is Decompression Sickness (DCS). DCS is an important risk for divers and manifestations of cognitive impairment need to be recognized earlier to prevent progression to a more severe stage. The literature used was collected from the Google Scholar, ScienceDirect, and PubMed databases with restrictions: publication year 2015-2025, Indonesian or English languages, and research with human subjects. The results of the literature review indicate that the pathophysiology of cognitive impairment after onset of DCS is still not clearly understood. The principles that are understood so far include the impact of nitrogen gas bubble circulation in cerebral arteries, extensive brain ischemia, white matter damage, and hyperbaric pressure administration can simultaneously improve cognitive function in patients. It can be concluded that neurological symptoms in DCS can develop into severe cognitive impairment if not recognized and treated immediately. The underlying relationship is mainly related to the impact of nitrogen gas embolism, cerebral ischemia, and extensive damage to cognitive areas of the brain.